The State's Responsibility in Ensuring Access to Education for Children with Special Needs in Remote Areas - Hasan Syahrizal; Fajrina Dhia Salsabila; Ainul Mardhiah (Yayasan pendidikan dzurriyatul Quran, 2026)
The fulfillment of the right to education for children with special needs in remote rural areas continues to face a gap between the normative guarantees provided by the national legal framework and the limited reality of educational access due to geographical barriers and weaknesses in local policy implementation. This study aims to analyze the state’s responsibility in ensuring access to education for children with special needs in the remote areas of Indragiri Hilir Regency, Riau Province, by examining the alignment between human rights principles, the national legal framework, and the practical implementation of education policies at the local level. The study employs a normative-empirical approach with a descriptive-analytical design, combining a review of statutory regulations and inclusive education policies with field data collection through semi-structured interviews, observations, and analysis of regional education planning documents. The findings indicate that although the state possesses a strong legal foundation for guaranteeing the educational rights of children with special needs, policy implementation in remote rural areas remains largely formalistic, as reflected in the limited availability of inclusive educational institutions, the shortage of specialized educators, weak needs-based planning, and underdeveloped public oversight and complaint mechanisms. The implications of this study highlight the importance of strengthening region-based affirmative policies, cross-sectoral integration, and the development of adaptive educational service models to ensure more responsive, inclusive, and equitable legal protection for children with special needs